ANALISIS SISTEM UPAH PADA KULI ANGKUT PASAR BEUREUNUEN - Mariana, Mariana; Safrijal, Safrijal (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
Labor and workers' wages are one of the central issues in today's industrial economy, where the majority of the population depends on the wages they earn, starting from low wage levels to the work contract system. All of this has become an issue that has sparked demonstrations among workers. Labor is not a simple resource to organize. Many factors influence these resources, such as the environment, local traditions, experience, age, leadership, wages, and so on. All these factors together form the complexity of managing a workforce. The aim of this research is to determine the wage practices of porters at the Beureunuen market and to analyze the pay system for porters at the Beureunuen market. The research method used is qualitative, by conducting field research using interviews, documentation and observation. The research results show that the practice of paying porters at Beureunuen Market is implemented using a daily wage payment system, taking into account the amount of repas. Wages are paid daily at a percentage of 15% of the repas, and the overall wages are divided equally among all the porters involved.